Evaluation of Distance Learning at Public Middle School Jakarta - Amirudin Amirudin; Siti Rochanah; Suryadi Suryadi (STAI Hubbulwathan Duri, 2021)
Distance learning is a solution to the conditions during the Covid-19 pandemic so that the educational process remains organized and productive. The purpose of the study was to obtain the results of the evaluation of distance learning at SMP Negeri Jakarta. This study used the descriptive qualitative method. Data collection techniques consist of observation, documentation, and interviews. The data collection process includes data collection, data reduction, data presentation, and concluding. The results of the study show that the implementation of distance learning still faces technical and non-technical obstacles, such as the readiness of facilities and infrastructure, teaching materials, readiness of students and parents in providing internet networks, pedagogical and professional competencies of teachers that are relevant to knowledge and technological advances. However, overall, distance learning activities have had a significant impact on the achievement of educational goals.